AGRICULTURE 5.0 POTENTIAL AND THE APPLICATION OF ADVANCED TECHNOLOGIES IN SERBIA - Bešić, Cariša; Ćoćaklo, Dragan; Bakator, Mihalj; Vidas-Bubanja, Marijana; Stanisavljev, Sanja (Economics of Agriculture, 2025)
This study explores key factors influencing Agriculture 5.0 adoption in Serbia, focusing on investment trends, government R&D funding, IoT adoption, and rural internet penetration. Data and literature analysis reveals that domestic investment and R&D spending drive digital transformation, and foreign investment remains volatile. IoT and internet expansion support smart farming but require further investment. Policy recommendations include strengthening digital infrastructure and increasing support for agricultural innovation. Future research should examine long-term investment impacts and sustainability benefits to improve Serbia’s transition to digital agriculture.